Management of patients on systemic steroids: An oral surgery perspective. (2nd October 2022) - Patel, Vikash; Nathwani, Shrina; Rahman, Naomi
Abstract : Corticosteroids are a common pharmacological treatment option used in a diverse range of clinical conditions. The diversity of guidance on their use has inevitably led to conflicting management plans between dental clinicians. For patients on long-term steroid cover, several guidelines highlight the importance of additional steroid prescribing during 'stressful' procedures. However, guidance on the definition of 'stressful' varies, as well as the recommended protocols. This article explores the existing evidence regarding steroid cover in patients taking long-term steroids, and proposes a protocol to help manage these patients in the dental environment. CPD/Clinical Relevance: An understanding of the clinical implications of long-term steroid use in patients requiring dental treatment, as well as the appropriate management protocols is important.